A MAN AT THE PERIPHERY OF WORld AND EXISTENCE: THE OVERCOMING OF LONELINESS - Филоненко, Александр (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The    article  explores  the  anthropological     contours   of  the  theological proposition to decentralize the “lifeworld (Lebenswelt)” in the act of the openness to God’s mercy. The author describes the topography of the existential periphery through the figures of beggar, thank-giver, singer, witness, judge,and compassionate and celebrating person. The article analyzes the consequences   of   such   anthropology   for   the   decentralization   of   culture through the practice of garden cultivation. The anthropology of Face and Personality is explored in the context of the response to the presence of the Other that unfolds itself through the explication of the responsivity stages.